Románia rendszerváltás utáni ipari szerkezetváltásának globális és regionális aspektusai - Molnár, Ernő (Közép-Európai Közlemények, 2010)
The change of the market economy and the economical structure of Romania caused the largescale cutting down of the industry which had been overdeveloped in the socialist period and had fought against numerous structural and qualitative problems. After the turn of the millennium, especially due to the foreign capital investment, reindustrialization was started and it caused that the Romanian industry has also an important role in the economy of Central and Eastern Europe nowadays. The renewal of the industry accompanied with structural change in the last year and resulted in both gaining ground of the transnational participants in Romania and in forging ahead of the export oriented machine production. The change of the industry is accompanied with serious structural changes in its regional distribution. The effect of the desindustrialization was felt in each region of the country but it caused the most serious problems in the monofunctional mining and the heavy industrial centres. The renewal of the industry shows greater concentration–according to regional preferences of the foreign direct investments: it forms a greater extent in Bucharest, in some more industrialized county of Muntenia, Banat and South Transylvania.